Knowledge Management in Universities: Role of Knowledge Workers - Hoq, Kazi Mostak Gausul; Akter, Rowshan (Bangladesh Journal of Library and Information Science, 2012)
Knowledge management has been hailed as one of the most important developments in the fields of information studies and management science in the recent decades. By capturing, organizing, documenting and sharing organisational knowledge, Knowledge management helps todays complex organisations to make better decisions and solve their problems effectively. As highest centers of learning, universities need to build information infrastructure and create a favourable atmosphere where teaching and non-teaching staff, students, researchers, patrons and other stakeholders can take part in various knowledge management activities. The role of knowledge workers in this regard is quite important. By advocating knowledge discovery and use, knowledge workers can bring about changes in the universitys organisational cultures and individual behaviors relative to knowledge. Universities can play a significant role in the building and unhindered development of a knowledge-based society by recruiting skilled and competent knowledge workers and empowering them to manage the knowledge assets effectively. Bangladesh Journal of Library and Information Science Vol.2(1) July 2012 pp.92-102 DOI: http://dx.doi.org/10.3329/bjlis.v2i1.12925